Centre for Mongol Studies - Шагдарсүрэн, Ц. (Acta Mongolica, 2002)
Thc Centre for Mongolian Studies (CMS) of the National University of Mongolia (NUM) was established in 2001, as a non-profit, non political, NUM component organisation interested in promoting and developing the study of the Mongolian language, history, literature and culture as well as the study of the nature of Mongolia and supporting the research activities of Mongolists abroad.